Dinamika Kolaborasi Guru Reguler dan Guru Pembimbing Khusus dalam Pendidikan Inklusi: Studi Kualitatif di SMP Kota Yogyakarta - Annisa Annisa; Dwi Putri Fatmawati; Luqman Hidayat; Rizki Aningrum (Jurusan Pendidikan Luar Biasa Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2026)
Although inclusive education in Indonesia continues to progress, studies on the dynamics of collaboration between general education teachers and special education teachers (GPK) remain limited, particularly at the secondary level. This study explores interaction patterns, role distribution, and challenges in teacher collaboration within inclusive junior high schools in Yogyakarta City. Using a descriptive qualitative approach through observation, interviews, and document analysis, the findings reveal that collaboration is still at an early stage, characterized by limited communication, minimal joint planning, and the absence of school policies regulating collaborative roles. Key barriers include time constraints, lack of training, and weak institutional support. The findings highlight the need to strengthen structural and cultural foundations of collaboration in inclusive schools. Theoretically, this study expands understanding of the social dimensions of teacher collaboration, while practically recommending integrated training and the development of school-based collaborative policies.